A Stylistic Analysis of For Whom the Bell Tolls - Kadir Mugair, Sarab; Jabber Khadum, Basima Abdul; Ali Khalaf, Hazim Mohamed (Opción, 2019)
The objective of this paper is to examine some stylistic features found in Ernest Hemingway’s novel “For Whom the Bell Tolls”, and to analyze further his specific style of writing and its special effect. This is accomplis- hed by utilising the theories of stylistics. A modified stylistic model of Leech (1969) is used for the purposes of linguistic analysis. The following aspects will be analyzed in the paper: the accepted feature of lexis; catego- ries of grammar; figures of speech; context and cohesion; and the writer’s linguistic preference linked to the theme. It is hoped that a more specific and a general idea can be derived on the influence of stylistics on the beauty and success of the writer. In fact, this study endeavours to find out Hemingway’s narative style that is extraordinary. The conclusion will be presented in the final section of the study.